A New Type of Efficient CO2 Adsorbent with Improved Thermal Stability: Self‐Assembled Nanohybrids with Optimized Microporosity and Gas Adsorption Functions. (8th April 2013) - Kim, Tae Woo; Kim, In Young; Jung, Tae Sung; Ko, Chang Hyun; Hwang, Seong‐Ju
Abstract A new type of efficient CO2 absorbent with improved thermal stability is synthesized via self‐assembly between 2D inorganic nanosheets and two kinds of 0D inorganic nanoclusters. In these self‐assembled nanohybrids, the nanoclusters of CdO and Cr2O3 are commonly interstratified with layered titanate nanosheets, leading to the formation of highly microporous pillared structure with increased basicity of pore wall. The co‐pillaring of basic CdO with Cr2O3 is fairly effective at increasing a proportion of micropores and reactivity for CO2 molecules and at improving the thermal stability of the resulting porous structure. Of prime importance is that the present inorganic‐pillared nanohybrids show highly efficient CO2 adsorption capacity, which is much superior to those of many other absorbents and compatible to those of CO2 adsorbing metal−organic framework (MOF) compounds. Taking into account an excellent thermal stability of the present nanohybrids, these materials are very promising CO2 adsorbents usable at elevated temperature. This is the first example of efficient CO2 adsorbent from pillared materials. The co‐pillaring of basic metal oxide nanoclusters employed in this study can provide a very powerful way of developing thermally stable CO2 adsorbents from many known pillared systems.